Between Scylla and Charybdis: Reflections on and problems associated with the evaluation of teachers in an era of metrification - Berliner, David C. (Education Policy Analysis Archives, 2018)
The Scylla and Charybdis in this discussion of teacher evaluation are standardized achievement test data on the one hand, and classroom observational systems on the other. These are the two most common methods used to judge teachers’ competency. Both have serious flaws: the former primarily with validity, the latter primarily with reliability. At most these evaluation strategies provide teachers’ and their supervisors information about which to converse. But these two methods have such serious flaws that they should never be used as the primary grounds for rewarding, punishing, or firing teachers. When both methods of evaluation are used to judge teacher competency, the correlation between achievement tests and observational data is quite low. When two methods claiming to assess the same construct do not correlate well, either one or both methods are failing to assess the intended construct. There are two alternatives for navigating between Scylla and Charybdis: “Duties Based Teacher Evaluation” and “Performance Measures.” These methods have much to recommend them, though like all methods of personnel evaluation, reliability and validity issues remain problematic.